2016
DOI: 10.1016/j.ejca.2016.08.024
|View full text |Cite
|
Sign up to set email alerts
|

The use of EORTC measures in daily clinical practice—A synopsis of a newly developed manual

Abstract: Cancer has increasingly become a chronic condition and the routine collection of patient-reported outcomes (PROs) like quality of life is widely recommended for clinical practice. Nonetheless, the successful implementation of PROs is still a major challenge, although common barriers to and facilitators of their beneficial use are well known. To support health care professionals and other stakeholders in the implementation of the EORTC PRO measures, the EORTC Quality of Life Group provides guidance on issues co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 83 publications
1
55
0
Order By: Relevance
“…In oncology, patient‐reported outcomes (PROs) have gained importance in patient‐centred health care and research, and PRO study end points complement traditional outcomes such as survival or disease progression . In routine clinical practice, PROs help to narrow the gap between patients' and health care professionals' (HCPs) view of health status and treatment success and help to improve care by meeting the patient's preferences and needs . Even in the context of advanced cancer settings, routine collection of PRO data has been shown to be feasible and associated with a number of clinical benefits including fewer hospitalizations and superior quality adjusted survival …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In oncology, patient‐reported outcomes (PROs) have gained importance in patient‐centred health care and research, and PRO study end points complement traditional outcomes such as survival or disease progression . In routine clinical practice, PROs help to narrow the gap between patients' and health care professionals' (HCPs) view of health status and treatment success and help to improve care by meeting the patient's preferences and needs . Even in the context of advanced cancer settings, routine collection of PRO data has been shown to be feasible and associated with a number of clinical benefits including fewer hospitalizations and superior quality adjusted survival …”
Section: Introductionmentioning
confidence: 99%
“…1 In routine clinical practice, PROs help to narrow the gap between patients' and health care professionals' (HCPs) view of health status and treatment success and help to improve care by meeting the patient's preferences and needs. [2][3][4] Even in the context of advanced cancer settings, routine collection of PRO data has been shown to be feasible and associated with a number of clinical benefits including fewer hospitalizations and superior quality adjusted survival. 5 However, the interpretation of scores derived from PRO questionnaires is often challenging for patients and HCPs, partly because results are given on metrics (eg, from 0 to 100 (6)) that often are difficult to interpret.…”
Section: Introductionmentioning
confidence: 99%
“…Patient-reported outcome measures (PROMs) complements clinical data with the patient's perspective, and there is an increasing demand for systematic implementation of PROMs in daily clinical practice and clinical trials. 15 It has therefore become important to develop PROMs that allow for broad cross-cultural application.…”
mentioning
confidence: 99%
“…The routine use of the EORTC QLQ-C30 in clinical practice appears to improve physician-patient communication and HRQoL [102], but the implementation has its challenges (e.g. timing, frequency, interpretations of scores by health care professionals, and the absence of thresholds for clinical importance) [103]. Surprisingly, the present review showed that the psychometric quality of this measurement instrument has been examined many times but not adequately in patients with advanced cancer.…”
Section: Discussionmentioning
confidence: 69%